The relationship between executive compensation and research and development spending: an analysis of medium and high-tech companies listed on the brazilian stock exchange - Borges, Ana Francyele Parente; Avila, Andressa Germann; Vendruscolo, Maria Ivanice; Kreuzberg, Fernanda; Victor, Fernanda Gomes (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2026)
Purpose: This study analyzes the relationship between executive compensation (fixed and variable) and research and development (R&D) spending—used as a proxy for innovation effort—in companies listed on the Brazilian stock exchange. The study examines how the incentive structure mitigates managerial risk aversion in sectors where innovation is strategic. The research guides the analysis of the relationship between executive compensation and the intensity of R&D investments in Brazilian medium-high and high-technology companies. Methodology: This research uses a quantitative, descriptive, and documentary approach, analyzing data from 53 publicly traded Brazilian companies between 2010 and 2022. The focus is on companies with medium-high and high levels of technological development, according to the classification of the Organisation for Economic Co-operation and Development (OECD), adapted by the Industrial Innovation Survey (PINTEC/IBGE). The data were analyzed using linear regression with panel data, controlling for variables such as size, indebtedness, profitability, and Covid-19. Results: The results demonstrate that the compensation structure influences managers' willingness to allocate resources to innovation. The findings indicate that, although there is a positive correlation between variable executive compensation incentives and R&D, this relationship is moderated by risk aversion and sectoral characteristics. This suggests that variable compensation acts as a partial mechanism to mitigate agency conflict, but its effectiveness depends on balancing it with short-term goals. Contributions of the Study: This research contributes to the literature by demonstrating how Agency Theory operates in an emerging market, where factors such as institutional instability influence managers' accounting choices. The study shows that, for high-tech companies in Brazil, aligning interests through executive compensation is crucial for sustaining long-term projects over immediate results.